Character Education in the Perspective of Humanistic Theory: A Case Study in Indonesia - Hartono, Yudi; Haryanto, Samsi; Asrowi, Asrowi (EDUCARE, 2018)
ABSTRACT: Character education has been an important agenda since the beginning of Indonesian independence. This article, based on the qualitative study and historical approach, tries to elaborate the character education in Indonesia. Findings show that the government policy in later periods affects the character education models in the schools. In the Old Order era, 1959-1966, especially in the Guided Democracy era, the character education had tended to be indoctrinated. Similarly, during the New Order era, 1966-1998, tend to be indoctrinated too. During the Reform era, 1998 to date, the character education is integrated into every lesson, self-development activities, and school culture. The learning model is given to the teachers. Teachers can develop innovative learning models according to student characteristics and learning needs. In the perspective of character education as a process of values education, the concept is initially a component that touches the philosophy of educational objectives of humanizing humans or humanistic learning. The learning models relevant to the concept are constructivist learning. With these models, students will discover and understand the values of the nations character as the basis for taking certain attitudes and actions through internalization process, i.e. the developmental change from externally controlled behavior to internally controlled behavior. Indoctrination models, such as in the Old Order era and New Order era in Indonesia, did not suitable with the humanistic philosophy of value education.KEY WORDS: Character Education; Indoctrination; Humanistic Theory; Indonesian Governments Policy; Learning Models.Â Â Â Â About the Authors: Yudi Hartono, M.Pd. is a Doctoral Student at the Study Program of Education Science FKIP UNS (Faculty of Teacher Training and Education, Sebelas Maret University), Jalan Ir. Sutami No.36-A Kentingan, Surakarta 57126, Central Java, Indonesia. Prof. Dr. Samsi Haryanto is a Professor Emeritus at the Departement of History FKIP UNS in Kentingan, Surakarta 57126, Central Java, Indonesia. Dr. Asrowi is a Lecturer at the FKIP UNS in Kentingan, Surakarta 57126, Central Java, Indonesia. Corresponding author is: yudihartono@student.uns.ac.idSuggested Citation: Hartono, Yudi, Samsi Haryanto & Asrowi. (2018). âCharacter Education in the Perspective of Humanistic Theory: A Case Study in Indonesiaâ in EDUCARE: International Journal for Educational Studies, Volume 10(2), February, pp.95-108. Bandung, Indonesia and BS Begawan, Brunei Darussalam: Minda Masagi Press owned by ASPENSI and BRIMAN Institute, ISSN 1979-7877. Article Timeline: Accepted (December 19, 2017); Revised (January 20, 2018); and Published (February 28, 2018).